Comprehensive evaluation of performance, combustion, and emissions of soybean biodiesel blends and diesel fuel in a power generator diesel engine - SAYIN, CENK (TAYLOR & FRANCIS INC, 2020)
In order to use the power generator diesel engine in fixed areas (University, hospital, school, official institutions) in case of electricity cut, it is necessary to test the usability of alternative fuel to diesel fuel with high performance and low emission. Therefore, experimental tests were conducted utilizing ultra-low sulfur diesel fuel (ULSD) and soybean biodiesel blends with ULSD in this manuscript. The combustion, exhaust emissions, and the performance values were gauged and compared to ULSD, SOB10 and SOB50 test fuels under 3.6 kW (lower load), 7.2 kW (medium load) and 10.8 kW (higher load) loads and constant high idling engine speed (1500 rpm) of a power generator diesel engine. The results of experiments demonstrated that the BSFC value at 10.8 kW load was compared with ULSD fuel, there was 6.3% increase in SOB50 fuel and 3.82% increase in SOB10 fuel at the same load and this increase was owing to lower heating value of biodiesel blends. Also, the results of experiments exhibited that utilizing biodiesel blends in diesel engine had approximately similar cylinder gas pressure, heat release rate, knock density, cumulative heat release and mean gas temperature when they were compared to ULSD running in diesel engine power generator. Biodiesel fuels that were compared with the emission values of ULSD; smoke opacity at 10.8 kW load minimum decrease 1.13%, unburned hydrocarbon at 3.6 kW load minimum increase 8% and carbon monoxide emissions were noticeably lessened as nitrogen oxides and carbon dioxide emissions increased in all loads.
Keywords: Power generator; soybean biodiesel; combustion; performance; emission; CALOPHYLLUM-INOPHYLLUM BIODIESEL; CEIBA-PENTANDRA OIL; EXHAUST EMISSIONS; INJECTION PRESSURE; OPTIMIZATION; SPRAY